Hardness and microstructure of 15H1M1FL steel after welding by the mode of the cross-section hill - Ефименко, Николай Григорьевич; Атоженко, Ольга Юрьевна; Кантор, Александр Геннадиевич (Eastern-European Journal of Enterprise Technologies, 2012)
When very thick 15Х1М1ФЛ (chrome-molybdenum-wolfram) method of hill without preheating or thermal treatment the bainite structure with the hardness below the allowable standard. After tempering the hardness (НАZ) remains higher than that of the parent metal